Rancang Bangun Aplikasi Penerjemah Bahasa Indonesia Bahasa Nias Menggunakan Algoritma Levensthein Distance - Laia, Aldi Irfan; Muliono, Rizki (Mahesa Research Institute, 2024)
In this context, there is a need for the development of a translator application that can translate between Indonesian and Nias languages. The aim of this research is to design and build an Android-based translator application that can translate text from Indonesian to Nias and vice versa.In this study, the Levenshtein Distance algorithm was used as a method to perform the translation process. This algorithm uses the calculation of the distance between two strings to identify the similarities and differences between words in Indonesian and Nias. Thus, the Levenshtein Distance can be used to produce accurate and relevant translation results.The design and development of the translator app was done using the Android platform as the development base. The application is designed to provide an intuitive and easy-to-use user interface, thus allowing users to quickly and efficiently translate texts into Indonesian and Nias languages. During the development process, the translator application was tested to ensure good quality and performance. The test results showed that the translation application was capable of producing accurate translations in accordance with the context of the Indonesian language and the Nias language. In conclusion, the research successfully designed and built an Android-based Indonesian-Nias language translator application using the Levenshtein Distance algorithm. This application is expected to be a useful tool in facilitating communication between Indonesian-speaking users and the Nias language. This research also contributed to the development of Nias-based translator applications that were still limited in previous literature.